2010
DOI: 10.1590/s0102-79722010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Subtestes semelhanças, vocabulário e compreensão do WISC-III: pontuação objetiva ou subjetiva?

Abstract: ResumoEste trabalho visou analisar a pontuação dos subtestes Semelhanças, Vocabulário e Compreensão do WISC-III, tendo em vista que podem envolver maior subjetividade do avaliador. Participaram do estudo 42 psicólogos de diferentes Estados do Brasil, os quais corrigiram as respostas de 6 protocolos do teste selecionados aleatoriamente da amostra de padronização ao contexto brasileiro. Tomando-se como referência os escores totais, o subteste Vocabulário apresentou maior variabilidade nas pontuações, seguido por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…Consequently, a number of delimiters were defined. The following exclusion criteria were applied to form a final pool of studies on examiner errors committed when a standard Wechsler battery was administered to an examinee, which characterizes applied practice: (a) studies of examiner errors on a single subtest or small group of subtests that did not combine to form a standard test battery (e.g., an examination of errors on the Similarities, Vocabulary, and Comprehension subtests only; Linger, Ray, Zachar, Underhill, & LoBello, 2007), (b) studies that used fabricated protocols (e.g., Hopwood & Richard, 2005), (c) studies in which the same protocols were scored by multiple raters (e.g., Brazelton, Jackson, Buckhalt, Shapiro, & Byrd, 2003; Oakland, Lee, & Axelrad, 1975), (d) studies reported solely in a foreign language (e.g., Figueiredo, Araújo, Dias, & Busetti, 2010), (e) studies in which some type of imputation procedure was applied to missing data prior to analyses (e.g., Faust, 2011), (f) studies in which graduate student examiner errors between a “business as usual” control group and an experimental condition not traditionally present in graduate coursework on intelligence testing (e.g., computer-assisted instruction, Hall, 1999; all protocols double-checked by graduate assistant prior to examination, Kuentzel, Hetterscheidt, & Barnett, 2011) were compared, and (g) studies that reported data in an unusable format (e.g., errors defined by scores on a test administration and scoring competency test, Blakely, Fantuzzo, & Moon, 1987). It should be noted that the aforementioned exclusion criteria are not mutually exclusive and some studies met more than one criterion (e.g., Bradley, Hanna, and Lucas, 1980) required all participants to score the same two fabricated protocols and subsequently recorded their errors).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, a number of delimiters were defined. The following exclusion criteria were applied to form a final pool of studies on examiner errors committed when a standard Wechsler battery was administered to an examinee, which characterizes applied practice: (a) studies of examiner errors on a single subtest or small group of subtests that did not combine to form a standard test battery (e.g., an examination of errors on the Similarities, Vocabulary, and Comprehension subtests only; Linger, Ray, Zachar, Underhill, & LoBello, 2007), (b) studies that used fabricated protocols (e.g., Hopwood & Richard, 2005), (c) studies in which the same protocols were scored by multiple raters (e.g., Brazelton, Jackson, Buckhalt, Shapiro, & Byrd, 2003; Oakland, Lee, & Axelrad, 1975), (d) studies reported solely in a foreign language (e.g., Figueiredo, Araújo, Dias, & Busetti, 2010), (e) studies in which some type of imputation procedure was applied to missing data prior to analyses (e.g., Faust, 2011), (f) studies in which graduate student examiner errors between a “business as usual” control group and an experimental condition not traditionally present in graduate coursework on intelligence testing (e.g., computer-assisted instruction, Hall, 1999; all protocols double-checked by graduate assistant prior to examination, Kuentzel, Hetterscheidt, & Barnett, 2011) were compared, and (g) studies that reported data in an unusable format (e.g., errors defined by scores on a test administration and scoring competency test, Blakely, Fantuzzo, & Moon, 1987). It should be noted that the aforementioned exclusion criteria are not mutually exclusive and some studies met more than one criterion (e.g., Bradley, Hanna, and Lucas, 1980) required all participants to score the same two fabricated protocols and subsequently recorded their errors).…”
Section: Methodsmentioning
confidence: 99%
“…Figuras) (CRUZ-RODRIGUES et al, 2014), superior à média(10) preconizada pelo manual.Um estudo argentino, envolvendo adolescentes e o uso de tecnologia de informação e comunicação -TIC -, percebeu que a média no subteste Semelhanças do WISC-III foi 10, mas as pontuações mais altas pertenciam aos indivíduos "menos expostos" às TIC (RAYNAUDO; BORGOBELLO, 2016). Um estudo português, envolvendo adolescentes institucionalizados com comportamento antissocial, obteve no WISC uma média de 8,88 e no WISC-III, 2,95 (MATOSO, 2014).O subteste Semelhanças é corrigido de forma quantitativa: acerto, acerto parcial e erro.Neste estudo, foi considerado apenas o total obtido pelo adolescente no subteste.…”
unclassified
“…Para a correção contamos com três juízes, uma vez em que, segundo Figueiredo et al (2010), o WISC-III se configura como um teste que conta para a maioria de seus itens com uma correção objetiva, no entanto no teste de Vocabulário os itens podem exigir julgamento subjetivo do examinador.…”
Section: Discussionunclassified